2021
DOI: 10.3390/fib9120080
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical Characterization of CFRPs under Elevated Temperatures for Strengthening Existing Structures

Abstract: Fiber-reinforced polymers (FRP) are rapidly gaining acceptance from the construction sector due to their large effectiveness. They are mainly used as confining reinforcement for concrete columns and as tensile reinforcement for concrete beams, columns and slabs. FRPs are already used to a large extent for applications such as bridges and parking lots, where elevated temperatures are not the main risk. Their increasing use as structural reinforcement is hampered by the concern related to their behavior at eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Higher values of strength and elongation were reported for specimens after ethylene oxide sterilization. Temperature-induced sterilization contributes to scission of the polymer chain, which results in reduced tensile strength and elongation (Otaguro et al , 2010; Papadimitriou et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Higher values of strength and elongation were reported for specimens after ethylene oxide sterilization. Temperature-induced sterilization contributes to scission of the polymer chain, which results in reduced tensile strength and elongation (Otaguro et al , 2010; Papadimitriou et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…This ideal elastic-brittle law is capable to replicate FRP's mechanical response with a rupture limit stress. The FRP sheets with thickness 0.13mm per sheet have a young's modulus 260GPa and a rupture stress equal to 2400MPa, according to experimental measurements available over the literature [9]. Again, the models are subjected to 3-point bending and the predicted behavior is compared with the virgin model (C0) in terms of load versus deflection curve, bending moment capacity and mode of failure.…”
Section: Methodsmentioning
confidence: 99%
“…Shell elements were used to represent the FRP sheets bonded to the concrete surface using cohesive interfaces. The FRP mechanical properties were derived by material testing [9], while the interface behavior was calibrated according to available information over the literature [2,6]. The validation of the numerical methodology used here is verified by a number of other publications [2,5,6,10].…”
Section: Introductionmentioning
confidence: 98%
“…Many studies showed that softening polymer matrix at elevated temperatures is the main reason causing the decrease in the mechanical properties of its composites. [26][27][28][29][30][31] Moreover, when the ambient temperature exceeds the T g , the mechanical properties of polymer composites degrade strongly because the polymer matrix losses robustly the strength and stiffness. As presented above, the T g of the CF/PA laminate is lower than 60°C.…”
Section: Temperature-dependent Compressive Properties Of the Cf/pa Co...mentioning
confidence: 99%
“…[25][26][27] The reduction in the mechanical properties of CFRPs at high temperatures can cause large deformations, the loss of reinforcement, and the eventual collapse of the CFRP structure. 28,29 Therefore, the time-temperature dependent behavior of CFRPs at elevated temperatures needs to be examined for their applications. [30][31][32] Nevertheless, most research on time-and temperature-dependent properties of CFRP laminates have been investigated under tensile and bending tests.…”
Section: Introductionmentioning
confidence: 99%